Evaluation of the process conditions for the production of microbial carotenoids by the recently isolated Rhodotorula mucilaginosa URM 7409 - Machado, Whallans Raphael Couto [UNESP]; Da Silva, Lucas Gomes [UNESP]; Vanzela, Ellen Silva Lago [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (FapUNIFESP (SciELO), 2019)
This study aimed to improve the physical and nutritional process conditions for the production of carotenoids by the newly isolated Rhodotorula mucilaginosa, a red basidiomycete yeast. The carotenoid bioproduction was improved using an experimental design technique, changing the process characteristics of agitation (130 rpm to 230 rpm) and temperature (25 °C to 35 °C) using seven experiments, followed by a 25-1 fractional design to determine the relevant factors that constitute the culture medium (glucose, malt extract, yeast extract, peptone and initial pH). A complete second order experimental design was then carried out to optimize the composition of the culture medium, the variables being yeast extract (0.5 to 3.5 g/L), peptone (1 to 5 g/L) and the initial pH (5.5 to 7.5), with 17 experiments. The maximum carotenoid production was 4164.45 μg/L (252.99 μg/g), obtained in 144 h in YM (yeast malt) medium with 30 g/L glucose, 10 g/L malt extract, 2 g/L yeast extract, 3 g/L peptone, an initial pH 6, 130 rpm and 25 °C, demonstrating the potential of this yeast as a source of bio-pigments. In this work, the nitrogen sources were the factors that most influenced the intracellular accumulation of carotenoids. The yeast R. mucilaginosa presented high production at a bench level and may be promising for commercial production.
Keywords: Basidiomycota; Experimental design; Optimization; Pigmented; Rhodotorula; Submerged culture; β-Carotene